2006
DOI: 10.1111/j.1524-4725.2006.32257.x
|View full text |Cite
|
Sign up to set email alerts
|

Pacemakers and Implantable Cardiac Defibrillators in Dermatologic Surgery

Abstract: The lack of complications associated with pacemakers and ICDs with electrosurgery is reassuring. The authors support published recommendations about techniques and precautions to optimize safety during electrosurgery in patients with cardiac devices. The care of patients with ICDs in particular requires special consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
(44 reference statements)
1
15
0
Order By: Relevance
“…However, a consistent finding among the studies was that a low anaerobic threshold was predictive of perioperative cardiovascular complications, 171,173,177 postoperative death, 172,174,175 or midterm and late death after surgery. 174,179,180 An anaerobic threshold of approximately 10 mL O 2 /kg/ min was proposed as the optimal discrimination point, with a range in these studies of 9.9 mL O 2 /kg/min to 11 mL O 2 / kg/min. Although exercise tolerance can be estimated from instruments such as the DASI 133 or the incremental shuttle walk test, in 1 study, a significant number of patients with poor performance by these measures had satisfactory peak oxygen consumption and anaerobic threshold on cardiopulmonary exercise testing.…”
Section: Exercise Stress Testing For Myocardialmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a consistent finding among the studies was that a low anaerobic threshold was predictive of perioperative cardiovascular complications, 171,173,177 postoperative death, 172,174,175 or midterm and late death after surgery. 174,179,180 An anaerobic threshold of approximately 10 mL O 2 /kg/ min was proposed as the optimal discrimination point, with a range in these studies of 9.9 mL O 2 /kg/min to 11 mL O 2 / kg/min. Although exercise tolerance can be estimated from instruments such as the DASI 133 or the incremental shuttle walk test, in 1 study, a significant number of patients with poor performance by these measures had satisfactory peak oxygen consumption and anaerobic threshold on cardiopulmonary exercise testing.…”
Section: Exercise Stress Testing For Myocardialmentioning
confidence: 99%
“…See Cardiopulmonary exercise testing has been studied in different settings, including before abdominal aortic aneurysm surgery [172][173][174]180 ; major abdominal surgery (including abdominal aortic aneurysm resection) [175][176][177] ; hepatobiliary surgery 178 ; complex hepatic resection 171 ; lung resection 181 ; and colorectal, bladder, or kidney cancer surgery. 179 These studies varied in patient population, definition of perioperative complications, and what was done with the results of preoperative testing, including decisions about the appropriateness of proceeding with surgery.…”
Section: Exercise Stress Testing For Myocardialmentioning
confidence: 99%
“…A survey by El-Gamal et al (2001) found that though no major adverse outcomes were reported by cutaneous surgeons using electrosurgical equipment, cardiac complications such as skipped beats or improper firing of an ICD were each seen at rates between 10 and 30% during dermatological procedures on the chest wall. Matzke et al (2006) performed a retrospective review at the Mayo Clinic of 173 patients with pacemakers and 13 with ICDs who underwent dermatologic surgery; the authors concluded that there were no documented complications related to bipolar electrosurgery.…”
Section: Complications From Pacing Wiresmentioning
confidence: 99%
“…A retrospective review of 173 patients with a pacemaker and 13 with an ICD who underwent Mohs or dermatologic excisional surgery involving electrosurgery was performed at the Mayo Clinic. 45 All patients had preoperative cardiology evaluation or device information reviewed by a staff member who deemed preoperative cardiology consultation unnecessary. Twelve of the 13 patients with an ICD underwent preoperative device deactivation with continuous intraoperative monitoring until postoperative device reactivation.…”
Section: Large Modern Series Of Emi In Cardiac Implantsmentioning
confidence: 99%